PENERAPAN FLY ASH SEBAGAI BAHAN SEMENTASI DALAM PENDEKATAN PERBAIKAN TANAH - Osok, Fidel Kalehangen; Simatupang, Minson (STABILITA || Jurnal Ilmiah Teknik Sipil, 2023)
One of the most commonly used approaches for soil stabilization, especially under buildings, is the grouting system. This approach usually uses additives, such as industrial by-product-fly ash. With this technique, fly ash solutions in various concentrations are injected into the sand samples. How far the spread of the fly ash solution from the point of injection was observed for each concentration of the solution. The results show that the higher the concentration of the solution, the smaller the spread of the fly ash solution. This is due to the agglomeration of the fly ash solution immediately in the sand pores around the injection point which will inhibit the spread of the solution. Even the smallest concentration of fly ash solution applied to the sand sample in the study was not able to spread throughout the sand. Another approach is needed so that the spread of the fly ash solution is maximized.